Use of RNAi With OsMYB76R as a Reporter for Candidate Genes Can Efficiently Create and Verify Gametophytic Male Sterility in Rice - Chen, Yun; Zhu, Wenping; Shi, Shudan; Wu, Lina; Du, Shuanglin; Jin, Liangshen; Yang, Kuan; Zhao, Wenjia; Yang, Jiaxin; Guo, Longbiao; Wang, Zhongwei; Zhang, Yi (Frontiers in Plant Science, 2021)
Gametophytic male sterility (GMS) plays an important role in the study of pollen development and seed propagation of recessive nuclear male sterile (NMS) lines insensitive to environmental conditions in hybrid rice breeding. Because of the inherent phenotypic and genetic characteristics of GMS, it is very difficult to find and identify the GMS mutants. However, due to the abundance of gene transcription data, a large number of pollen-specific genes have been found, and most of them may be associated with GMS. To promote the study of these genes in pollen development and heterosis utilization, in this study an easy and efficient method of creating and identifying GMS was established using RNAi and OsMYB86R as reporter. First, the OsC1/OsMYB86 gene involved in anthocyanin synthesis was modified, and we have validated the modified OsMYB86R is workable as the same as the pre-modified OsMYB86 gene. Then, the ascorbic acid oxidase gene OsPTD1 was downregulated using RNAi, driven by its own promoter, which resulted in abnormal pollen tube growth. Finally, the RNAi elements were linked with OsMYB86R and transformed into an osmyb86 mutant, and the distortion of purple color segregation was found in T1 and F1 generations. This indicates that the OsPTD1 GMS was successfully prepared. Compared to current methods, there are several advantages to this method. First, time is saved in materials preparation, as one generation less needs to be compared than in the conventional method, and mutation screening can be avoided. In addition, for identification, the cost is lower; PCR, electrophoresis, and other processes are not needed; and no expensive chemicals or instruments are required. Finally, the results are more accurate, with much lower background effects, and no damage to the plant. The result is an easy, efficient, low-cost, and accurate method of preparing and identifying GMS genes.